Rapid nano-gram scale screening method of micro-arrays to evaluate drug-polymer blends using high-throughput printing technology - Taresco, Vincenzo; Louzao, Iria; Scurr, David J.; Turpin, Eleanor R.; Laughton, Charles A.; Alexander, Cameron; Burley, Jonathan C.; Garnett, Martin (American Chemical Society, 2017)
A miniaturized, high-throughput assay was optimized to screen polymer-drug solid dispersions using a 2-D Ink-jet printer. By simply printing nanoliter amounts of polymer and drug solutions onto an inert surface, drug:polymer micro-dots of tunable composition were produced in an easily-addressable micro-array format. The amount of material printed for each dried spot ranged from 25 ng to 650 ng. These arrays were used to assess the stability of drug:polymer dispersions with respect to recrystallization, using polarized light microscopy. One array with a panel of 6 drugs formulated at different ratios with Poly (vinylpyrrolidone-vinyl acetate) copolymer (PVPVA) was developed to estimate a possible bulk (gram-scale) approximation threshold from the final printed nano amount of formulation. Another array was printed at a fixed final amount of material to establish a literature comparison of one drug formulated with different commercial polymers for validation. This new approach may offer significant efficiency in pharmaceutical formulation screening, with each experiment in the nano-micro-array format requiring from 3 up to 6 orders of magnitude lower amounts of sample than conventional screening methods.